Histological skeletochronology indicates developmental plasticity in the early Permian stem lissamphibian Doleserpeton annectens. Issue 4 (6th February 2020) - Gee, Bryan M.; Haridy, Yara; Reisz, Robert R.
Abstract: Doleserpeton annectens is a small‐bodied early Permian amphibamiform, a clade of temnospondyl amphibians regarded by many workers to be on the lissamphibian stem. Most studies of this taxon have focused solely on its anatomy, but further exploration of other aspects of its paleobiology, such as developmental patterns, is critical for a better understanding of the early evolutionary history of lissamphibians. Here, we present a histological analysis of growth patterns in D. annectens that utilizes 60 femora, the largest sample size for any Paleozoic tetrapod. We identified pervasive pairs of closely spaced lines of arrested growth (LAGs), a pattern that indicates a marked degree of climatic harshness and that would result in two cessations of growth within a presumed single year. We documented a wide degree of variation compared to previous temnospondyl skeletochronological studies, reflected in the poor correlation between size and inferred age, but this observation aligns closely with patterns observed in extant lissamphibians. Furthermore, sensitivity analyses conducted by subsampling our dataset at more typical sample sizes for paleontological studies produced a wide range of results. This includes biologically improbable results and exceptionally well‐fit curves that demonstrate that low sample size can produce potentially misleading artifacts. We propose that the weak correlation between age and size represents developmental plasticity in D. annectens that typifies extant lissamphibians. Detection of these patterns is likely only possible with large sample sizes in extinct taxa, and low sample sizes can produce false, misleading results that warrant caution in drawing paleobiological interpretations from such samples. Abstract : This manuscript presents a skeletochronological examination of growth patterns of the early Permian stem lissamphibian Doleserpeton annectens . Through the largest sample size for any Paleozoic tetrapod ( n  = 60), we identify patterns of developmental plasticity in response to climatic harshness and seasonality that mirror the patterns seen in crown lissamphibians.